A Time Allocation and the Demand, Production and Supply of Labour in Households - Jankiewicz , Jacek (Studia Oeconomica Posnaniensia, 2014)
This article presents the basic assumptions of the household production function theory, a concept which assigns a key role to time allocation in all consumer behaviours. It also presents arguments in favour of the need for conducting regular time use surveys of Polish households. Empirical tests evaluating the quality of prediction for this model require access to statistics on the time use of the population. Such surveys are currently conducted in more and more countries around the world. In Poland, the availability of statistical data on household time allocation seems to be highly unsatisfactory. The author is of the opinion that the publication of the results of only one complete survey on the time use of the population during a period of almost 25 years of socio-economic transformation indicates a significant gap in statistical resources. Thus, the possibility of conducting some valuable analyses, such as those relating to the labour market, in a large European economy under transformation has been forfeited.